PENGALAMAN TENAGA KESEHATAN DALAM MERAWAT IBU HAMIL DENGAN PREEKLAMSIA DI KABUPATEN JEMBER - Bachrul Ulum; Dini Kurniawati; Eka Afdi Septiyono (Indonesian National Nurses Association (INNA) of Central Java, 2023)
Preeclampsia is a pathologic condition occurred in pregnancy commonly characterized by blood pressure elevation, proteinuria, and peripheral edema. Preeclampsia is a serious condition and potentially could be fatal to mother and fetal condition without proper and prompt management. The aim of this study is to explore healthcare provider experience in the management of preeclampsia among pregnant women in Jember Regency, East Java. This study was conducted using qualitative method with phenomenology approach to explore healthcare providers’ experience. Participants in this study consisted from 10 healthcare providers which work at the local public health center’s maternal and children health unit. Data related to healthcare providers’ experiences were collected and explored using qualitative interview and analyzed using Collaizi method. Data analysis results showed that there were several factors which support and inhibit healthcare provider efforts to prevent and manage preeclampsia. These findings highlight the obstacle and phenomena experienced by healthcare providers in the field, which could be used to evaluate and improve current strategies used in prevention and management of preeclampsia.